MEASURING THE EFFECTIVENESS OF ELECTRONIC WORD-OF-MOUTH AND BRAND IMAGE IN SHAPING PURCHASE INTENTION - Angga Kurniawan; Nelson Lajuni; Tasrim Tasrim; Cyntiani Putri; Ali Mufti Hasyim Kurniawan (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
This study aims to analyze the effects of Electronic Word of Mouth Effect, Brand Image, and Email Marketing on Purchase Intention in the context of purchasing official MotoGP merchandise. It was conducted among respondents who are members of large motorcycle communities in Indonesia with a high interest in MotoGP, but who never purchased official merchandise. Its data were collected through a questionnaire using a Likert scale and analyzed using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method. The results indicate that the Electronic Word of Mouth Effect has a positive influence on Purchase Intention. The consumers’ recommendations, reviews, and digital communication play an important role in shaping purchase intentions toward MotoGP merchandise. Email Marketing has a positive influence on Purchase Intention, confirming the effectiveness of direct and personalized marketing communication in encouraging purchase interest. Yet, brand Image does not show a significant effect on Purchase Intention. It indicated that the MotoGP brand image has not become a dominant factor for consumers who lack prior purchasing experience. These findings emphasize the importance of optimizing digital marketing strategies based on Electronic Word of Mouth and Email Marketing to enhance consumers’ purchase intentions toward MotoGP merchandise.